Characterization of light intensity and quality, vegetative, flowering and fruiting traits in high and super-high density olive hedgerows - Ladux, Federico J.; Rousseaux, María Cecilia; Trentacoste, Eduardo Rafael (Elsevier, 2024)
Orchard design (intra- and inter-row distance) defines the space allotted to each tree and the light environment for growth in olive hedgerows. Shading between neighboring trees affects the light intensity and quality, modifying the tree vegetative, flowering and fruiting characteristics. In this study, the incident photosynthetically active radiation (PAR) was simulated and the red-to-far-red ratio (R/FR) reflected by neighboring hedgerows down the canopy walls was measured. An analysis is presented of the response of olive vegetative, flowering, fruiting and productive traits to hedgerows of high (HD) and super-high density (SHD) orchards. The study was carried out during the 2018–2019 and 2019–2020 seasons in two 10-year-old olive cv. Genovesa orchards, one in HD (7 x 3.5 m) and the other in SHD (4 x 1.5 m). In both systems, continuous rows were used for measurements of light environment and vegetative, flowering and fruiting characteristics. The R/FR ratio and mean daily horizontal incident PAR were significantly higher in HD than in SHD. One-year-old shoots of HD hedgerows had shorter internodes in L position than U, M and L positions of SHD. Inflorescence number per shoot in the M and L positions of HD were triple than those of corresponding positions of SHD hedgerows. The mean yield per ha for both seasons was similar between HD and SHD hedgerows (average 9.3 and 9.4 t/ha, respectively). A greater planting density in olive hedgerows reduces the R/FR ratio reflected by neighboring trees while reducing incident PAR with increases in the hedgerow height. As a result, more illuminate HD hedgerows have greater specific leaf mass, higher leaf area density and higher axis-order angle compared to SHD hedgerows. This study seeks a new way to understand and measure the suitability of an olive cultivar trained in hedgerows at different planting densities.